Ortaöğretim Öğrencileri İçin Değerlendirme Deneyimi Ölçeğini Uyarlama Çalışması. - Kahraman, Emine; Koray, Özlem; Turan, Seçil; Çolakoğlu, Özgür Murat (Electronic Turkish Studies, 2020)
In education, the experiences of students related to factors such as students, teachers, teaching methods, teaching materials. What students experience in the process; the amount and distribution of study efforts, examinations and learning, assignments and learning are included in the assessment process. In this context, the lack of a valid and reliable instrument that can measure the assessment experience of existing students to determine the amount of study and the nature of the assignments is remarkable. In this study, the Assessment Experience Questionnaire(AEQ), originally developed by Gibbs and Simpson (2003), was adapted to Turkish. The study is important in terms of being a source of data and providing the students' current assessment experiences. During the scale development process, additional items were included to the scale by literature review and final version of it was formed. The study group of the study consisted of 222 students for the first application and 1041 students for the last application. The AEQ consists of three subdimensions; the amount and distribution of the study effort, the examination and learning, assignments and learning. Some items have been eliminated from the adapted instrument because loading of the factors that make up the factors into more than one factor, factor load values are at least 3 items, and statistically, factorforming substances are theoretically in the same factor structure. Data were analyzed by exploratory factor analysis using the SPSS. To conduct the reliability and validity analyses of the scale, item analysis, factor analysis, and reliability coefficient were found. A scale of 13 items was formed from the item pool consisting of 31 items before the application of the scale. The adapted scale can be used to reveal the assessment experiences of different groups of students.